2019
DOI: 10.7554/elife.42819
|View full text |Cite
|
Sign up to set email alerts
|

Shank3 modulates sleep and expression of circadian transcription factors

Abstract: Autism Spectrum Disorder (ASD) is the most prevalent neurodevelopmental disorder in the United States and often co-presents with sleep problems. Sleep problems in ASD predict the severity of ASD core diagnostic symptoms and have a considerable impact on the quality of life of caregivers. Little is known, however, about the underlying molecular mechanisms of sleep problems in ASD. We investigated the role of Shank3, a high confidence ASD gene candidate, in sleep architecture and regulation. We show that mice la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 85 publications
6
70
0
Order By: Relevance
“…A disruption in excitation/inhibition balance may also alter network properties such as brain rhythms. Indeed, altered EEG rhythms, including an increase in gamma power, have been observed in Shank3 -mutant mice (Han et al, 2013; Wang et al, 2016; Dhamne et al, 2017; Ingiosi et al, 2019; Yoo et al, 2019) as well as in SHANK3 -related ASD and PMS (Soorya et al, 2013; Holder and Quach, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A disruption in excitation/inhibition balance may also alter network properties such as brain rhythms. Indeed, altered EEG rhythms, including an increase in gamma power, have been observed in Shank3 -mutant mice (Han et al, 2013; Wang et al, 2016; Dhamne et al, 2017; Ingiosi et al, 2019; Yoo et al, 2019) as well as in SHANK3 -related ASD and PMS (Soorya et al, 2013; Holder and Quach, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus appears particularly susceptible to the effects of acute sleep deprivation with sleep deprivation affecting gene expression, kinase signaling pathways, spatial memory consolidation, synaptic plasticity and neuronal structure [10][11][12][13][14][15][16][17]. The hippocampus is not the only brain region affected by sleep deprivation, as studies of the cortex and forebrain also reported changes in gene expression after sleep deprivation [18][19][20][21]. Despite the widespread transcriptional changes induced by sleep deprivation and the severity of the impact on memory, the mechanisms by which sleep deprivation adversely impairs neuronal function have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep analysis is highly Ube3am-/p+ exhibited less spindles, as we hypothesized given the reduction in sleep spindles observed clinically in AS [43]. Fewer, abnormal sleep spindles have been historically implicated in intellectual disabilities [55,56] and for numerous genetic NDDs, such as Phelan-McDermid and Prader-Willi syndromes [57,58] as well as childhood epilepsies [59] [60] and ASDs [61,62]. Sleep spindles have been reported altered when mGluR5 is deficient [63], mGluR5 dysregulation has been postulated as underlying Fragile X Syndrome phenotypes, another NDD with ASD and poor sleep regulation [64,65].…”
Section: Discussionmentioning
confidence: 95%